CYBER ESPIONAGE IN JORDANIAN PENAL LEGISLATION - Dr-Ibtisam Saleh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this study, we will address the most serious electronic crime against information security and the security of individuals, which is cyber espionage according to the Jordanian criminal legislation. The Jordanian legislation has dealt with espionage crimes in the Protection of State Secrets and Documents Law No. (50) 1971, and addressed cyber espionage in Article (12) of the Electronic Crime Law. In order for an understanding of Article 12 to be straightforward, it is necessary to begin with a clarification of the concept of espionage and in particular cyber espionage and mention its forms. And then address espionage crimes according to the Protection of State Secrets and Documents law in terms of their forms, which are limited to three crimes: 1- entry or attempting to enter prohibited places, 2- theft and obtaining state secrets, 3- reporting or disclosing state secrets which could be obtained by holding a specific post. In addition to clarifying the extent of the possibility of committing these crimes by electronic means. Subsequently, we provided an explanation of the cyber espionage stipulated in Article 12 of the Electronic Crime Law, in which we clarified its three pillars; the physical aspect, the subject of the crime and the moral aspect, and we clarified the penalties imposed on the perpetrators of electronic espionage. Finally, the researcher presents a number of results that are rational based on the topic of the current study.